Pengembangan Media Pembelajaran Model Tutorial Berbasis Pendekatan Saintifik: Penelitian - Dewi Leni Mastuti; Saptiana Sulastri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The research was conducted with the aim of developing tutorial-based learning media using a scientific approach and its impact on learning activities and improving student learning outcomes on the topic of writing short stories. The method used in this research is the Research and Development method with a development design based on the Hannafin and Peck model. According to the research objectives, the data sources used in this study were obtained from the validation questionnaire of the media's feasibility, as well as observations of learning activities and student learning outcome tests. The subjects in this study were students of class XI at SMKN 3 Singkawang. The results indicated an increase in the average student learning outcomes from the initial test score of 61.75 to 82.95 in the final test. Based on observations of activities, the average frequency of student learning activities was 78.04, categorized as good, and based on testing using effect size, a value of 2.36 was obtained, categorized as large. It can be concluded that the tutorial-based learning media with a scientific approach has a significant impact on increasing student activity and learning outcomes.